Fatores de risco para transmissão da hanseníase : um estudo caso controle em um município endêmico no interior do Estado do Espírito Santo - Santos, Andréia Soprani dos (2007)
Leprosy in Brazil became a public health problem, taking into consideration the high degree of endemism of the disease in many states of Brazil. The state of Espírito Santo (ES) shows significant rates of detection and prevalence of the disease, reason why it has made efforts in order to eliminate the grievance. The present study aims to identify of the individuals risk factors relation to the transmission of leprosy in the endemic district in the countryside of ES. A study case-controlled was developed, having the group cases represented by the new cases of leprosy sick people pontificated at SINAN during 2003 and 2006 and a group controlled made up of the healthy people living near the cases, pared by sex and age. The study information was taken out of interviews following a questionnaire with open and closed questions, made in the residence of the participants. Ninety patients and 270 controls were interviewed. The age varied between 6 to 84 years old, with average of 42, 8 years old. The residence medium size was around 52, 8 m². The average value for the alcohol drink use was 48, 3 ml/week and for tobacco 13, 7 cigarettes/day. In the labor activity, 93 (25, 8%) were housewives, 79 (21, 9%) rural workers, 51 (14, 2%) retired and 15 (4, 2%) laborers. There was as a relevant association between the occurrence of the disease and the current presence of leprosy among co-sanguine parents (OR= 2, 9) and old cases of leprosy among co-sanguine parents (OR= 5,0). Considering the complexity of the leprosy epidemiology and the long period of the disease incubation it is suggested the accomplishment of new studies aiming at identifying factors of risk associated with the disease transmission. Knowing that the only exam of the contact in the act of the diagnostic detects a minimum part of the new cases, it is proposed, based on the present study results, the accomplishment of periodical examinations in the ones whose parents are contaminated with leprosy, to detect the cases which would appear in the years to come after the contact.